The placenta, maternal diet and adipose tissue development in the newborn - Symonds, Michael E.; Bloor, Ian; Ojha, Shalini; Budge, Helen (Karger, 2017)
Background: A majority of adipose tissue present in the newborn possess the unique mitochondrial protein, uncoupling protein (UCP1). It is thus highly metabolically active and capable of producing 300 times more heat per unit mass than any other organ in the body. The extent to which maternal obesity and/or an obesogenic diet impacts on placental function thereby resetting the relative distribution of different types of fat in the fetus is unknown. Summary: Developmentally the majority (if not all) fat in the fetus can be considered as classical brown fat, in which UCP1 is highly abundant. In contrast, beige (or recruitable) fat which possess 90% less UCP1 may only appear after birth, as a majority of fat depots undergo a pronounced transformation that is usually accompanied by the loss of UCP1. The extent to which this process can be modulated in a depot-specific manner and/or changes in the maternal metabolic environment remain unknown. Key Messages: An increased understanding of the mechanism by which offspring born to mothers possess excessive adipose tissue could enable sustainable interventions designed to promote the abundance of UCP1 possessing adipocytes. Ultimately, this would increase their energy expenditure and improve glucose homeostasis in these individuals.